A glance into traditional pig slaughtering practices in Vietnam and opportunities for zoonotic disease prevention - Ting, Nancy I.; Dang-Xuan, Sinh; Gilbert, Jeffrey; Nguyen, Nguyen Thao Thi; Lam, Steven; Nguyen-Viet, Hung (Frontiers in Sustainable Food Systems, 2023)
African swine fever in Vietnam isare contributing to existing concerns over zoonotic disease transmission from sick pigs to humans. While slaughterhouses are key sites of occupational hazards to workers and contamination of meat, the specific slaughtering practices contributing to zoonotic occupational and foodborne disease risks remain under-researched. Our objective is to identify and characterize aspects of pig slaughtering processes that contribute to such risks. To do so, we draw on qualitative observations, photos, and videos from three mobile slaughterhouses and seven abattoirs in Hung Yen, Vietnam. Based on our analysis, areas likely leading to zoonoticoccupational and foodborne disease risks include slaughtering procedures, personal hygiene of workers, equipment sanitation, and facility sanitation. Within the small-scale swine industry, slaughtering practices are long-standing and difficult to change. Our study underscores the importance of hygiene training of workers, improvements to and regulation of equipment and facilities, and awareness-building activities targeting consumers to reduce the burden of zoonotic disease risks in informal slaughterhouse settings.